Graphene negative electrode lead paste for lead storage battery and preparation method of graphene negative electrode lead paste
By reasonably setting the additive ratio and preparation steps, the problem of additive clustering in graphene negative lead paste is solved, the visual density and filling effect of lead paste are improved, and excellent battery performance is achieved.
Patent Information
- Application Number
- CN202510144824.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-11
AI Technical Summary
In existing lead-acid batteries, the additives are prone to clusters when preparing graphene negative lead paste, and it is difficult to mix evenly and disperse evenly, affecting the visual density and filling effect of lead paste of lead paste.
By reasonably setting the amount of additives such as graphene, acetylene black, humic acid, lignin, staple fiber, barium sulfate, DCA lignin, and using steps such as preparing slurry, dry mixing, paste, wet mixing, acid mixing, etc., to ensure that the additives are evenly dispersed and the apparent density of lead paste is increased.
The visual density of the lead paste of graphene negative lead paste is within the range of 4.40-4.46g/cm3, which meets the standards and has excellent lead paste filling effect.
Smart Images

Figure BDA0005266119470000101 
Figure BDA0005266119470000102 
Figure BDA0005266119470000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of storage batteries, and in particular relates to a graphene negative electrode lead paste for a lead-acid battery and a preparation method thereof. Background Art
[0002] Lead-acid batteries are widely used in automobile starting, energy storage systems and other fields due to their low cost, high reliability and mature technology. Its basic structure includes a positive electrode (lead dioxide), a negative electrode (lead) and an electrolyte (dilute sulfuric acid). Lead paste is a key material for the electrode. It is a mixture of lead powder, sulfuric acid, additives, etc., coated on the electrode substrate, and solidified to form an active substance. Lead powder is the active substance, sulfuric acid participates in the electrochemical reaction, water adjusts the fluidity of the lead paste, and additives improve the performance. The negative electrode lead paste undergoes the conversion of lead and lead sulfate during the charging and discharging process, and its performance directly affects the capacity, cycle life and power output of the battery.
[0003] Traditional lead paste has the following problems: poor conductivity: the conductivity of lead is limited, which affects the power output of the battery; large volume change: the conversion of lead and lead sulfate during the charge and discharge process causes volume change, which can easily cause damage to the electrode structure; short cycle life: volume change and sulfation phenomenon shorten the battery life; low energy density: the high density of lead limits the energy density of the battery.
[0004] Graphene has become an ideal material for improving the performance of lead paste due to its excellent conductivity, mechanical strength and chemical stability. Introducing graphene into negative electrode lead paste can significantly improve battery performance. When preparing graphene negative electrode lead paste, additives such as acetylene black, humic acid, lignin, short fibers, barium sulfate, etc. are generally added as auxiliary materials. The preparation method is usually to add the auxiliary materials into a paste mixer, then add lead powder for dry mixing, then add pure water for wet mixing, then add acid for acid mixing, and finally mix and stir evenly to make a graphene negative electrode lead paste suitable for filling and coating that meets the lead paste apparent density standard.
[0005] When preparing graphene negative electrode lead paste in the existing process, additives such as acetylene black, humic acid, lignin, short fibers, and barium sulfate are added to the lead paste. There is a problem that the additives are easy to agglomerate and difficult to mix and disperse evenly, which will affect the apparent density of the graphene negative electrode lead paste and result in poor filling effect of the lead paste. Summary of the invention
[0006] The object of the present invention is to provide a graphene negative electrode lead paste for a lead-acid battery and a preparation method thereof, so as to solve the problem that additives are easy to agglomerate and difficult to be uniformly mixed and dispersed when preparing the graphene negative electrode lead paste.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a graphene negative electrode paste for a lead-acid battery, wherein graphene, acetylene black, humic acid, lignin, short fibers, barium sulfate, and DCA lignin are added as additives.
[0009] Furthermore, the graphene negative electrode lead paste also contains lead powder, deionized water and acid.
[0010] Furthermore, the graphene negative electrode lead paste contains 6-8 parts of graphene, 0.2-0.4 parts of acetylene black, 0.4-0.6 parts of humic acid, 0.1-0.2 parts of lignin, 0.1-0.2 parts of short fibers, 0.3-0.5 parts of barium sulfate, and 0.2-0.3 parts of DCA lignin by weight.
[0011] Furthermore, the graphene negative electrode lead paste also contains 75-80 parts of lead powder, 10-12 parts of deionized water and 3-5 parts of acid.
[0012] Further, the acid is 1.2 g / mL of dilute sulfuric acid.
[0013] In a second aspect, the present invention provides a method for preparing graphene negative electrode lead paste for lead-acid batteries, comprising the steps of S1, preparing slurry; S2, dry mixing; S3, mixing paste; S4, wet mixing and acid mixing.
[0014] Further, S1, the specific steps of preparing the slurry are:
[0015] Graphene, acetylene black, humic acid, lignin, and DCA lignin were first mixed with deionized water and stirred for 5-7 minutes to prepare a slurry.
[0016] Further, the specific steps of S2, dry mixing are:
[0017] When preparing lead paste, first add a portion of lead powder into the paste mixing machine, then add short fibers and barium sulfate, and then add the remaining lead powder, and dry mix for 5-7 minutes.
[0018] Further, the specific steps of S3, the paste preparation are as follows:
[0019] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry.
[0020] Further, the specific steps of S4, wet mixing and acid mixing are:
[0021] After the slurry is added and stirred, deionized water is added to the paste mixer for wet mixing for 3-5 minutes, acid is added for acid mixing for 1-3 minutes, and finally mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention can improve the apparent density of the graphene negative electrode lead paste by reasonably setting the amount of additives such as graphene, acetylene black, humic acid, lignin, short fibers, barium sulfate, DCA lignin, etc.
[0024] (2) The present invention obtains graphene negative electrode lead paste by reasonably setting the preparation steps, thereby solving the problem that additives are easy to agglomerate and difficult to mix and disperse uniformly when preparing graphene negative electrode lead paste; it is determined that the apparent density of the graphene negative electrode lead paste prepared in the embodiment of the present invention is in the range of 4.40-4.46 g / cm 3 , in line with the lead paste apparent density standard, and has excellent lead paste filling effect. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] This embodiment provides a graphene negative electrode lead paste for a lead-acid battery, which is prepared by the following steps:
[0028] S1. Preparation of slurry:
[0029] 6 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 5 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0030] S2. Dry mixing:
[0031] When preparing the lead paste, first add 25 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0032] S3, ointment:
[0033] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0034] S4, wet mix, acid mix:
[0035] After the slurry is added and stirred, 5 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, and 3 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes. Finally, the mixture is mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0036] Example 2
[0037] This embodiment provides a graphene negative electrode lead paste for a lead-acid battery, which is prepared by the following steps:
[0038] S1. Preparation of slurry:
[0039] 7 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 5 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0040] S2. Dry mixing:
[0041] When preparing the lead paste, first add 25 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0042] S3, ointment:
[0043] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0044] S4, wet mix, acid mix:
[0045] After the slurry is added and stirred, 5 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, and 3 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes. Finally, the mixture is mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0046] Example 3
[0047] This embodiment provides a graphene negative electrode lead paste for a lead-acid battery, which is prepared by the following steps:
[0048] S1. Preparation of slurry:
[0049] 8 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 5 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0050] S2. Dry mixing:
[0051] When preparing the lead paste, first add 25 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0052] S3, ointment:
[0053] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0054] S4, wet mix, acid mix:
[0055] After the slurry is added and stirred, 5 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, and 3 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes. Finally, the mixture is mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0056] Example 4
[0057] This embodiment provides a graphene negative electrode lead paste for a lead-acid battery, which is prepared by the following steps:
[0058] S1. Preparation of slurry:
[0059] 8 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 5 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0060] S2. Dry mixing:
[0061] When preparing the lead paste, first add 27 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0062] S3, ointment:
[0063] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0064] S4, wet mix, acid mix:
[0065] After the slurry is added and stirred, 5 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, and 3 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes. Finally, the mixture is mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0066] Example 5
[0067] This embodiment provides a graphene negative electrode lead paste for a lead-acid battery, which is prepared by the following steps:
[0068] S1. Preparation of slurry:
[0069] 8 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 5 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0070] S2. Dry mixing:
[0071] When preparing the lead paste, first add 30 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0072] S3, ointment:
[0073] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0074] S4, wet mix, acid mix:
[0075] After the slurry is added and stirred, 5 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, and 3 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes. Finally, the mixture is mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0076] Example 6
[0077] S1. Preparation of slurry:
[0078] 8 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 5 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0079] S2. Dry mixing:
[0080] When preparing the lead paste, first add 30 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0081] S3, ointment:
[0082] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0083] S4, wet mix, acid mix:
[0084] After the slurry is added and stirred, 6 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, and 3 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes. Finally, the mixture is mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0085] Example 7
[0086] S1. Preparation of slurry:
[0087] 8 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 6 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0088] S2. Dry mixing:
[0089] When preparing the lead paste, first add 30 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0090] S3, ointment:
[0091] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0092] S4, wet mix, acid mix:
[0093] After the slurry is added and stirred, 6 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, and 3 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes. Finally, the mixture is mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0094] Example 8
[0095] S1. Preparation of slurry:
[0096] 8 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 6 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0097] S2. Dry mixing:
[0098] When preparing the lead paste, first add 30 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0099] S3, ointment:
[0100] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0101] S4, wet mix, acid mix:
[0102] After the slurry is added and stirred, 6 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, 4 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes, and finally mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0103] Example 9
[0104] S1. Preparation of slurry:
[0105] 8 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, and 0.25 parts of DCA lignin were first mixed with 6 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0106] S2. Dry mixing:
[0107] When preparing the lead paste, first add 30 parts of lead powder into the paste mixing machine, then add 0.15 parts of short fibers and 0.4 parts of barium sulfate, and then add 50 parts of lead powder, and dry mix for 5-7 minutes;
[0108] S3, ointment:
[0109] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0110] S4, wet mix, acid mix:
[0111] After the slurry is added and stirred, 6 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, and 5 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes. Finally, the mixture is mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0112] Comparative Example 1
[0113] This comparative example provides a graphene negative electrode lead paste for a lead-acid battery, which is prepared by the following steps:
[0114] S1. Preparation of slurry:
[0115] 10 parts of graphene, 0.5 parts of acetylene black, 0.3 parts of humic acid, 0.3 parts of lignin, and 0.1 parts of DCA lignin were first mixed with 7 parts of deionized water and stirred for 5-7 minutes to prepare a slurry;
[0116] S2. Dry mixing:
[0117] When preparing the lead paste, first add 25 parts of lead powder into the paste mixing machine, then add 0.3 parts of short fibers and 0.2 parts of barium sulfate, and then add 60 parts of lead powder, and dry mix for 5-7 minutes;
[0118] S3, ointment:
[0119] Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry;
[0120] S4, wet mix, acid mix:
[0121] After the slurry is added and stirred, 7 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, 2 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes, and finally mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0122] Comparative Example 2
[0123] This comparative example provides a graphene negative electrode lead paste for a lead-acid battery, which is prepared by the following steps:
[0124] S1. Dry mixing:
[0125] Add 6 parts of graphene, 0.3 parts of acetylene black, 0.5 parts of humic acid, 0.15 parts of lignin, 0.25 parts of DCA lignin, 0.15 parts of short fibers and 0.4 parts of barium sulfate into a paste mixer and stir for 5-7 minutes; then add 75 parts of lead powder and dry mix for 5-7 minutes;
[0126] S2, wet mix, acid mix:
[0127] After the dry mixing is completed, 10 parts of deionized water are added to the paste mixer for wet mixing for 3-5 minutes, 3 parts of 1.2 g / mL dilute sulfuric acid are added for acid mixing for 1-3 minutes, and finally mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.
[0128] The graphene negative electrode lead pastes prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were tested for apparent density of the lead pastes. The specific test method is as follows:
[0129] Use a cylindrical lead paste apparent density measuring cup with a known weight W1 and internal volume V after accurate measurement, take lead paste from three different positions in the pot and put it into the cup and compact it, scrape off the excess lead paste at the mouth from the center to the surroundings with a small spatula, scrape the lead paste at the mouth flat, and then scrape off the excess lead paste on the outer wall with a small spatula, and then use an electronic scale to accurately weigh the total weight W2;
[0130] The apparent density of lead paste is calculated as follows:
[0131]
[0132] Where ρ 密 - Apparent density of lead paste, in g / cm 3 ;
[0133] W1- empty cup weight of apparent density measurement cup, in g;
[0134] W2-total weight of the apparent density measuring cup after filling with lead paste, in g;
[0135] V-apparent density measurement cup internal volume, unit is cm 3 .
[0136] Table 1
[0137]
[0138]
[0139] It can be seen from Table 1 that the apparent density of the graphene negative electrode lead paste prepared in Examples 1 to 9 of the present invention is in the range of 4.40-4.46 g / cm 3 , in line with the lead paste apparent density standard, and has excellent lead paste filling effect.
[0140] Compared with Example 1, Comparative Example 1 changes the amount of each additive, which is not within the scope of the present invention. It is determined that the apparent density of the graphene negative electrode lead paste is lower. Compared with Example 1, Comparative Example 2 changes the preparation steps, directly adds the additives into the paste mixer, then adds lead powder for dry mixing, then adds deionized water for wet mixing, then adds acid for acid mixing, and finally mixes and stirs evenly to obtain the graphene negative electrode lead paste. It is determined that the apparent density of the graphene negative electrode lead paste prepared by this method is also lower.
[0141] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0142] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A graphene negative electrode lead paste for a lead-acid battery, characterized in that: The graphene negative electrode lead paste is added with graphene, acetylene black, humic acid, lignin, short fibers, barium sulfate, and DCA lignin as additives.
2. The graphene negative electrode lead paste for lead-acid battery according to claim 1, characterized in that: The graphene negative electrode lead paste also contains lead powder, deionized water and acid.
3. The graphene negative electrode lead paste for lead-acid battery according to claim 1, characterized in that: The graphene negative electrode lead paste contains 6-8 parts of graphene, 0.2-0.4 parts of acetylene black, 0.4-0.6 parts of humic acid, 0.1-0.2 parts of lignin, 0.1-0.2 parts of short fibers, 0.3-0.5 parts of barium sulfate, and 0.2-0.3 parts of DCA lignin by weight.
4. The graphene negative electrode lead paste for lead-acid battery according to claim 1, characterized in that: The graphene negative electrode lead paste also contains 75-80 parts of lead powder, 10-12 parts of deionized water and 3-5 parts of acid.
5. The graphene negative electrode lead paste for lead-acid battery according to claim 4, characterized in that: The acid was 1.2 g / mL dilute sulfuric acid.
6. A method for preparing a graphene negative electrode lead paste for a lead-acid battery according to any one of claims 1 to 5, characterized in that: The method comprises the steps of S1, preparing slurry; S2, dry mixing; S3, mixing paste; and S4, wet mixing and acid mixing.
7. The method for preparing a graphene negative electrode lead paste for a lead-acid battery according to claim 6, characterized in that: S1. The specific steps of preparing the slurry are: Graphene, acetylene black, humic acid, lignin, and DCA lignin were first mixed with deionized water and stirred for 5-7 minutes to prepare a slurry.
8. The method for preparing a graphene negative electrode lead paste for a lead-acid battery according to claim 6, characterized in that: S2. The specific steps of dry mixing are: When preparing lead paste, first add a portion of lead powder into the paste mixing machine, then add short fibers and barium sulfate, and then add the remaining lead powder, and dry mix for 5-7 minutes.
9. The method for preparing a graphene negative electrode lead paste for a lead-acid battery according to claim 6, characterized in that: S3, the specific steps of the paste are: Pour the slurry in S1 into an ultrasonic container to dissolve and disperse for 5-10 minutes to obtain a dispersed slurry, and then add the dispersed slurry into a paste mixer by spraying, stirring while adding the slurry, and continue stirring for 3-5 minutes after adding the slurry.
10. The method for preparing a graphene negative electrode lead paste for a lead-acid battery according to claim 6, characterized in that: S4. The specific steps of wet mixing and acid mixing are: After the slurry is added and stirred, deionized water is added to the paste mixer for wet mixing for 3-5 minutes, acid is added for acid mixing for 1-3 minutes, and finally mixed and stirred for 5-7 minutes to obtain the graphene negative electrode lead paste.